Significance of Focal EEG Abnormalities in Pervasive Developmental Disorder and ADHD - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2012)
Researchers at University of Fukui, Japan analyzed the relation between EEG abnormalities and PDD or ADHD, and assessed the clinical utility of EEG in the differential diagnosis of these disorders.